The expression you want to simplify is 0-(x-y).
0-(x-y)
=-(x-y)
=-x+y
You just have to treat the negative sign in front of (x-y) as a -1 and distribute it to both x and -y.
There's a key problem in this question compelling you to actually rewrite it like that! Mathematically that is inaccurate and incorrect. If you do 72(8+19) it seems as if you are going to do 8+19*72 as in algebra whatever is outside the bracket is bound to go multiplied so technically (8+19)+72 would make more sense and the answer is
Using bidmas do the brackets first
8+19= 27
27+72=99
Answer: $14.40
10% of $18 = $1.80 (just divide it by 10)
$1.80 x 2 = $3.60
20% of $18 = $3.60
since it’s a discount, you subtract from the original price so:
$18 - $3.60 = $14.40
Answer:
11.3353
Step-by-step explanation:
please mark me brainliest.
I am begging